Similarities and Differences in Left Ventricular Size and Function among Races and Nationalities: Results of the World Alliance Societies of Echocardiography Normal Values Study - Asch, Federico M.; Miyoshi, Tatsuya; Addetia, Karima; Citro, Rodolfo; Daimon, Masao; Desale, Sameer; Fajardo, Pedro Gutierrez; Kasliwal, Ravi R.; Kirkpatrick, James N.; Monaghan, Mark J.; Muraru, Denisa; Ogunyankin, Kofo O.; et al. (Journal of the American Society of Echocardiography, 2019)
The World Alliance Societies of Echocardiography (WASE) Normal Values Study evaluates individuals from multiple countries and races with the aim of describing normative values that could be applied to the global community worldwide and to determine differences and similarities among people from different countries and races. The present report focuses specifically on two-dimensional (2D) left ventricular (LV) dimensions, volumes, and systolic function. The WASE Normal Values Study is a multicenter international, observational, prospective, cross-sectional study of healthy adult individuals. Participants recruited in each country were evenly distributed among six predetermined subgroups according to age and gender. Comprehensive 2D transthoracic echocardiograms were acquired and analyzed following strict protocols based on recent American Society of Echocardiography and European Association of Cardiovascular Imaging guidelines. Analysis was performed at the WASE 2D core laboratory and included 2D LV dimensions, LV volumes, and LV ejection fraction (LVEF) by the biplane Simpson method and global longitudinal strain (GLS). Two thousand eight subjects were enrolled in 15 countries. The median age was 45 years (interquartile range, 32–65 years), 42.8% were white, 41.8% were Asian, and 9.7% were black. LV dimensions and volumes were larger in male subjects, while LVEF and GLS were higher in female subjects. Global WASE normal ranges for LV dimensions were smaller than those in the guidelines, but the upper limits of normal for LV volumes and the lower limits of normal for LVEF were higher in the WASE study. Significant intercountry variation was identified for all LV parameters reflecting LV size (dimensions, mass, and volumes) even after indexing to body surface area, with LV end-diastolic and end-systolic volumes having the highest variation. The largest volumes were noted in Australia, while the smallest were measured in India for both genders. This finding suggests that in addition to gender and body surface area, specific country should be considered when evaluating LV volumes. Intercountry variation for LVEF and GLS was smaller but still statistically significant (P < .05 for all). LV dimensions and volumes are larger in men, while LVEF and GLS are higher in women. Current guideline-recommended normal ranges for LV volumes and LVEF should be adjusted. Intercountry variability is significant for LV volumes, and therefore nationality should be considered for defining ranges of normality. •LV dimensions and volumes are larger in males,LVEF and GLS are higher in females.•Guideline-recommended normal ranges for LV volumes and EF should be revised.•Due to Inter-country variability nationality should be considered for defining ranges of normality for LV volumes.•Dimensions and volumes are similar for people of White and Black race, while smaller for Asians and Mexicans (mixed white/native American race).•Given national variations within same race, adjustments of normal ranges by nationalities seem more appropriate than by race.